Universalitas Dan Partikularitas Hak Asasi Manusia Dalam Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Abdullah Tri Wahyudi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2016)
Human rights are a fundamental right or fundamental rights of existing and human beings, often called the human rights (human rights). So human rights are basic rights or the rights of human subjects brought from birth as a gift / gift of God Almighty. This right is fundamental in nature and is a natural right that can not be separated from and in human life. Marriage is a basic human right that is rights to form families in marriage and with their particularities in the Marriage Act which regulates marriage, will result in their universality and particularity of human rights in the regulation of marriage in Indonesia. Universality and particularity of human rights in Law No. 1 Year 1974 on Marriage. So this study can answer the question about how the universality of human rights in Law No. 1 Year 1974 on Marriage and how the particularity of human rights in Law No. 1 Year 1974 on Marriage.